(untitled) (Modern information system and technologies, 2018)
The article examines the microcontroller system for the construction of unmanned aerial vehicles (hereinafter referred to as UAV) based on Arduino Mega 2560. The selection of electronic components for the creation of this system has been analyzed and justified. Demonstrated variants of the construction, advantages and methods of using these UAVs.